2017
DOI: 10.1590/1807-3107bor-2017.vol31.0090
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and adipokines after periodontal therapy in patients with Type 2 diabetes and chronic periodontitis

Abstract: Abstract:The mechanism by which chronic periodontitis (CP) affects type 2 diabetes (T2DM) remains unclear. Therefore, the aim of this study is to evaluate the effects of periodontal therapy (PT) on the glycemic control and adipokines of patients with T2DM and CP with the purpose of elucidating the possible mechanisms by which CP influences T2DM. Forty-four patients with T2DM and CP were randomly divided into two groups according to whether they underwent PT. Periodontal status, blood glucose, and the levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…However, the reduction of HbA1c level did not meet the target of American Diabetes Association treatment goal that the HbA1c level must be reduced to less than 7.5 in healthy older people 12 . In other previous studies [24][25][26][27] , periodontal therapy in diabetic patients could signi cantly reduce HbA1c levels from 0.29-0.64% in 3-month and 0.2% in 6-month after completion of the therapy 28 . As the combination of lifestyle changes and dental care program also decreased HbA1c (0.29%) after 3-months follow-ups, whereas the HbA1c increased 0.09% in the control group 19 .…”
Section: Discussionmentioning
confidence: 79%
“…However, the reduction of HbA1c level did not meet the target of American Diabetes Association treatment goal that the HbA1c level must be reduced to less than 7.5 in healthy older people 12 . In other previous studies [24][25][26][27] , periodontal therapy in diabetic patients could signi cantly reduce HbA1c levels from 0.29-0.64% in 3-month and 0.2% in 6-month after completion of the therapy 28 . As the combination of lifestyle changes and dental care program also decreased HbA1c (0.29%) after 3-months follow-ups, whereas the HbA1c increased 0.09% in the control group 19 .…”
Section: Discussionmentioning
confidence: 79%
“…Sample size calculation was done based on the previous papers by Wang et al,2017 andŠimják et al,2018; that reported the difference in FGF-21 level between diabetic patients with periodontitis and healthy controls to be 100±70 pg/mL. 14 patients were needed to detect that difference using power 95% and 5% significance level.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…On the other hand, Teshome and Yitayeh, (2016) performed a meta-analysis, and the results revealed a statistically significant HbA1c reduction of 0.48 (95% CI: 0.18, 0.78) in the treatment group when compared with the control group. Similarly, Wang et al, (2017) showed that the intervention group showed a significantly greater change in the HbA1c level, which indicated that periodontal treatment, may improve the glycemic control. Accordingly, whether periodontal therapy reduces the HbA1c level in periodontitis patients still remain controversial.…”
Section: Resultsmentioning
confidence: 82%
“…However, even after treatment, FGF21 level showed a significantly higher values in the diabetic group than the non-diabetic periodontitis group. Conversely, a study performed by Wang et al, (2017) found that the serum FGF21 levels was significantly increased after therapy, which indicated that the effective control of inflammation by periodontal therapy may contribute to increasing systemic insulin-sensitizing adipokines, such as FGF21, thus in turn improving the overall health status. This discrepancy might be explained that, in the current study, the increase in crevicular FGF21 before treatment might act as a protective mechanism to oppose periodontal inflammation and as the inflammation subsided after treatment, the need for such protection is receded.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation